Musicking Poulenc’s ruins in Stellenbosch - Pauw, Marietjie (Acta Academica: Critical views on society, culture and politics, 2017)
This article investigates several performances of a flute solo (written by Francis Poulenc) as presented by the author in Stellenbosch, South Africa.1 Un joueur de flûte berce les ruines was written in the 1940s, ‘discovered’ in the late 1990s by Ransom Wilson and published in 2000 by Chester. The title of the solo carries an unidentified reference to the ‘serenading’ of ‘ruins’. This title, the shrouded originating circumstances of Poulenc’s composition, as well as its only-recent appearance, are central to the subsequent argument for music curations ‘after sound’ (Barrett). Douglas Barrett’s notion of ‘critical music’ directs this reflexive article enquiry. Curations ‘after sound’ take place when music compositions operate on platforms of socio-critical arts practice. ‘Musicking’, proposed by Christopher Small, probes the question: ‘What’s really going on here?’ The article asks this question by reflecting on the intentional juxtapositions of time, place and context that occurred when the author presented the solo on performances respectively titled ‘Die Vlakte’, ‘Roesdorp’, and ‘Portrait’. The article analyses aspects of films by Aryan Kaganof (2016) that responded to the ‘Roesdorp’ performance and suggests that the films manifest as Rancière-ian ‘aesthetics as politics’: they expose and intertwine layers of complicity, critique, confusion and care. A fleeting juxtaposition of silence and echo as metaphorical extensions to the notion of ‘after sound’ concludes this article enquiry.